2004
DOI: 10.1177/104063870401600404
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Age, Sex, and Production Class on Liver Zinc Concentration in Calves

Abstract: Abstract. Determination of zinc concentrations in the liver of calves and young stock is commonly requested by practitioners and nutritionists to assess whether they receive an appropriate amount of zinc in their diet. However, interpretation of liver zinc concentrations is currently based on information reported for adult cattle for which the health status was unknown and irrespective of production class, sex, and age. A retrospective study of necropsy reports was undertaken to assess the relationships betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…The mean (SEM) liver zinc wet weight concentrations of the placebo, zinc Met, and ZO treated calves at exit were 145.3 (95.6), 179.1 (114.4), and 137.6 (72.3) mg/kg, respectively, which are below reported mean liver zinc wet weight concentrations of 345.7 (16.1) mg/kg in neonatal Holstein calves with clinical signs of zinc toxicosis (Graham et al, 1988). It has been reported in calves up to one year of age, without clinical signs of zinc deficiency or toxicosis, that acceptable liver zinc concentrations range from 49 to 117 mg/kg wet weight (Puschner et al, 2004a). Based on these data, calves in our trial did not have liver zinc concentrations suggestive of zinc deficiency (24-28 mg/kg wet weight) or toxicosis, but it is possible that there is a wide range of liver zinc concentrations during the first three weeks of life, from birth to weaning, and from weaning to breeding age.…”
Section: Elisa Status At Enrollmentmentioning
confidence: 70%
See 1 more Smart Citation
“…The mean (SEM) liver zinc wet weight concentrations of the placebo, zinc Met, and ZO treated calves at exit were 145.3 (95.6), 179.1 (114.4), and 137.6 (72.3) mg/kg, respectively, which are below reported mean liver zinc wet weight concentrations of 345.7 (16.1) mg/kg in neonatal Holstein calves with clinical signs of zinc toxicosis (Graham et al, 1988). It has been reported in calves up to one year of age, without clinical signs of zinc deficiency or toxicosis, that acceptable liver zinc concentrations range from 49 to 117 mg/kg wet weight (Puschner et al, 2004a). Based on these data, calves in our trial did not have liver zinc concentrations suggestive of zinc deficiency (24-28 mg/kg wet weight) or toxicosis, but it is possible that there is a wide range of liver zinc concentrations during the first three weeks of life, from birth to weaning, and from weaning to breeding age.…”
Section: Elisa Status At Enrollmentmentioning
confidence: 70%
“…The National Research Council (NRC) daily zinc recommendation for calves is 40 mg/kg of total diet. There is a significant effect of age on liver zinc concentrations in calves in that the liver zinc concentrations decrease with time after birth (Puschner et al, 2004a). The low levels found in colostrum and milk replacer may reflect adequate tissue reserves of zinc in the bovine neonate (Abdelrahman and Kincaid, 1993;NRC, 2001).…”
Section: Elisa Status At Enrollmentmentioning
confidence: 99%
“…Young animals have a greater need for iron and zinc compared to older animals [1, 20]. This may be the biological explication for the higher liver concentrations typically found in young animals compared to older animals [21, 22]. The zinc level steadily drops from birth until 2 years because growing animals need more zinc than non-growing animals [23].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding Zn concentration in liver, it is possible that its low concentration [compared with values reported by Puls (1994)] is related to the young age of the animals. Puschner et al (2004) observed that Zn concentrations in the liver of calves increased with age. Hepatic Se concentration was considered the best predictor of fetal Se status due to the high correlation between maternal and fetal Se in liver (Gooneratne et al, 1989;Van Saun et al, 1989).…”
Section: Liver Accumulationmentioning
confidence: 94%